Diagnosis by metagenomic next-generation sequencing of a Talaromyces marneffei bloodstream infection in an HIV-negative child: A case report - Aimei Yang; Yan Hu; Peiling Chen; Guilang Zheng; Xuejiao Hu; Jingwen Zhang; Jing Wang; Chun Wang; Zijian Huang; Yuxin Zhang; Yuxiong Guo (Frontiers Media S.A., 2022)
BackgroundTalaromyces marneffei (TM) bloodstream infections are life- threatening in immunocompromised individuals. The lack of specific clinical features for these infections and poor sensitivity associated with routine examination procedures make diagnosis challenging. Untimely diagnosis and delayed antifungal treatment threatens the life of such patients.Case descriptionWe report a case of a TM bloodstream infection, confirmed by the results of blood culture, of a child who was HIV negative and possessed a CD40LG gene mutation. A diagnosis of TM was established by blood metagenomic next-generation sequencing (mNGS) of the patient's blood, which was confirmed by microbiological culture of blood. On admission, this previously healthy male patient was 8-months of age, who presented with recurrent fever and a cough of 6-days in duration. His condition did not improve after antibacterial treatment for 5-days, with significant and recurrent fever and worsening spirit. He was referred to the Department of Pediatrics in our tertiary medical institution with a white blood cell count of 21.5*10∧9/L, C-reactive protein of 47.98 mg/L, and procalcitonin of 0.28 ng/mL. A bloodstream infection was not excluded and blood was collected for microbial culture. The patient received a 1-day treatment of cefoperazone sulbactam and 6-days of imipenem cilastatin. Symptoms did not improve and fever persisted. Blood was submitted for mNGS analysis and within 14-h, 14,352 TM reads were detected with a relative abundance of 98.09%. Antibiotic treatment was immediately changed to intravenous amphotericin B combined with oral itraconazole. The condition of the child gradually improved. Blood culture showed TM on the 7th day after hospitalization, confirming bloodstream infection. After the 13th day of hospital admission, the patient's body temperature dropped close to 38°C and was discharged on the 30th day of hospitalization. Oral itraconazole was prescribed with follow up at the outpatient clinic.ConclusionsHIV-negative patients with CD40LG mutations may be potential hosts for TM. TM infections are rare in children and their detection by conventional microbial culture methods are inadequate for an early diagnosis. mNGS is a rapid detection method that permits early diagnosis of uncommon infectious agents, such as TM, allowing for improved patient outcomes.